Frammenti di un discorso politico-culturale. Il 68 nel 2018, tra democrazia di qualità e politica anti-sistema - Nevola, Gaspare (SocietàMutamentoPolitica, 2018)
The 1968 is a symbolic date that refers to a specific year but also and mostly to an entire historical period. The identitary characters of this historical season changes depending on which national, political and cultural contexts or aspects we decide to rebuild or remember. The phenomenology of the “long 68” refers to a striking multiplicity of levels: generational and values ones as well as mentality and customs, or economy, politics, ideology. But during 50 years we observe also a changing of the political culture that has processed the “68 public memory”. That is why historiography, political science and sociology fail to offer stable lectures of the 68. Here we try to historicise and periodize the “italian long 68”. We distinguish “three 68”: 1) the “spring-summer 68” (1966-69); 2) the “autumn 68” (1969-72); 3) the “winter 68” (1972-78). We underline that the “second 68” is the decisive one to understand the entire 68 parabola: from “active idealism” of student movement to “anni di piombo” of terrorist armed struggle. This essay does not propose conclusive answears about the meaning of the 68 season: here we are interested not so much “to close the discourse on 68” but rather to reopen it. This last is a task for post-68 generations. Looking at our 68 heritage give us fruithfull arguments and a base to understand the contemporary world, its “democratic malaise”, the chiaroscuri of the post-68 political culture of “adaptive civicness” as well as the current times characterized by a new and different wave of anti-system politics. If we are able in reading “68 today” with “differente eyes” we can find direction of analysis of our “strange democracy” and so light up where we are, where do we go or where we would like to go.